Numerical Analysis of Shear Behavior of High-Strength Reinforced Concrete Columns - Teddy Yustiono; Harun Alrasyid; Pujo Aji; Yu Chen-Ou; Yusronia Putri (Institut Teknologi Sepuluh Nopember, 2017)
Although the utilization of high-strength concrete and high-strength steel can reduced column dimension at high-rise building, the column aspect ratio remain low. These column were tended to dominate by shear failure than flexure failure. The research discusses the numerical analysis of shear critical of High-strength reinforced concrete columns. The Uniaxial Shear Flexure Method (USFM) was used to observe this behavior and examined on the test result. This study showed that USFM method provided conservative prediction. Some modification was proposed in order to improve this method when estimate the shear behaviour of high-strength reinforced concrete column.